Perception and Awareness of Animal Welfare Among Residents of Malta - Pantaleo Gemma; Eleonora Nannoni; Barbara Padalino; Angelo Peli; Francesco Luca Alexander; Giovanni Buonaiuto; Luca Sardi; Giovanna Martelli (Animals)
A representative sample of Maltese citizens (N = 384) was surveyed about their perception and attitude towards animal welfare and animal-friendly foods. Knowledge about animal welfare was self-evaluated as moderate (36%) or good (27%), and mass media (television, web and newspapers) were the primary information source (73%). Dairy cows were perceived as having the highest welfare (average rating 3 on a 1-to-5 scale), while conditions for broilers and pigs were perceived as more critical (average rating 2.7). Respondents consider animal welfare important (64%), the availability of welfare-friendly products in Malta limited (49%), and would support a national animal-friendly label (84%). Although 49% were willing to pay more for animal-friendly products, the accepted price increase was limited (increase below 10% for 37% of respondents, 20% were not willing to pay more and 27% were price-sensitive). Chi-squared analysis showed that the respondents’ profession impacted the support towards an animal welfare label (p < 0.01), with business operators being the least interested. Urban respondents were more critical toward farm animal welfare and more supportive of establishing a national welfare label than rural respondents (p < 0.05). The latter were less convinced that their choices can influence the welfare of farm animals (p < 0.01). Women were more willing to pay for welfare improvements than men (p < 0.01). These findings emphasize a significant concern for animal welfare among respondents, coupled with a moderate willingness to pay. The strong support for a national animal welfare label warrants the question as to whether transparent labelling would allow consumers to translate their sensibility into ethical purchasing behaviour.